Evaluation of the Program of Acceleration of Learning: a strategic appraisal towards inclusive education in the post-conflict process - Ortiz, Lina Maria; Betancourt, Carolina (Universidad Pedagógica y Tecnológica de Colombia, 2020)
In Colombia, the Ministry of National Education has adopted the Program of Acceleration of Learning [PAL], as a flexible model for people in special conditions. The study assessed the PAL in an educational institution from the city of Neiva, to determine whether the objectives for which it was implemented are being achieved, and whether the program can be a reference for the population that emerges from the post-conflict process. The approach of the study was qualitative, with a descriptive-evaluative scope, and cross-sectional, taking data between the years 2011-2016. Since the study evaluates the impact of the aforementioned program, the design of non-experimental cross-sectional research was adopted. To that end, documentary review and interviews were carried out. It was found that the PAL has guaranteed re-entry into the education system at the level of basic education, but it does not guarantee continuity in secondary education, due to different reasons that cause school dropout. The PAL can be classified as feasible for population that arises from the post-conflict process.